Fabrication And Characterization Of Electrospinning Biodegradable Fabric Layer For Face Mask Application - Zawawi, Nur’ain Syakirah (Universiti Sains Malaysia, 2022)
The increased use of 3-ply facemasks has raised concerns about the pollution they cause to the environment. The non-biodegradability of current 3-ply facemasks is highlighted because it is difficult to manage the waste and much more pollution is created when facemasks are discarded. Several studies have been conducted in order to improve the filtration layer on a consistent basis by using biodegradable polymers as an alternative. The present study aimed to fabricate polylactic acid (PLA), poly (butylene adipate-co-terephthalate) (PBAT) and PLA/PBAT fibre mat layers. The effect of different needle sizes on the properties and morphology of PLA and PBAT fibre mats was identified by using the Scanning Electron Microscope (SEM) tabletop, ImageJ and Universal Tensile Machine (UTS). In addition, the effect of single and binary solvents was investigated to produce PLA/PBAT fibre mat layer. Results showed that small size needles produced small-diameter fibres. The best needles to use for the fabrication of the PLA and PBAT fibre mats are 25G and 23G, respectively based on the fibre diameter and tensile properties. A 25G needle produced the smallest diameter and compact fibre mat. However, a 21G needle produced a PLA fibre mat with the highest tensile strength and Young’s modulus. On the other hand, a 25G needle is the best needle size to produce a PBAT fibre mat with good tensile properties. Binary solvents using DCM and DMF produced continuous and thinner fibres and showed higher tensile properties compared to the single solvent system.